Optimised real-time rendering of auditory events in immersive virtual environments - Gorzel, Marcin (Trinity College (Dublin, Ireland). Department of Electronic & Electrical Engineering, 2014)
This project looks at the problem of the capture or synthesis of acoustic events in reverberant spaces and their subsequent plausible reproduction in a virtual version of the original space, otherwise known as a Virtual Auditory Environment (VAE). Of particular concern is identification and perceptually accurate reconstruction of the important acoustic cues that enable us to localise sound sources in the whole 3-D space, with a special emphasis on the perception of auditory distance.
Keywords: Electronic and Electrical Engineering, Ph.D.; Ph.D. Trinity College Dublin